Transformed images of women in a Sundanese magazine; A corpus linguistics perspective - Yuliawati, Susi (Wacana, Journal of the Humanities of Indonesia, 2025)
In this paper, I examine the evolving portrayal of women in Sundanese society through a close analysis of certain nouns denoting women in the magazine Manglé. Using corpus linguistics, specifically word frequency and collocation analyses, I aim to investigate the evolving images of Sundanese women in relation to Indonesia’s political context over time. I argue that the evolution shown can be seen as a detailed overview of how the images of Sundanese women have been transformed. The results indicate that the trend in constructing women’s images is predominantly through the use of the noun wanoja, in contrast to other nouns. Through this noun, women are increasingly portrayed as possessing greater confidence to engage in the public sphere. In addition to spotlighting Sundanese women’s discussion, this paper can also serve as a representative case of how corpus linguistics research can be applied to other Sundanese texts or other regional texts in Indonesia.